Application Management c - Keuper, Frank; Oecking, Christian; Degenhardt, Andreas; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
A number of eminent authors take a look at aspects of application management from a range of practical and theoretical perspectives and present possible solutions for current challenges, demonstrating the close links between service creation and service management. Contents Cloud Computing Service Creation and Quality Management Resource and Competency Management Strategic Management Knowledge Management Target groups (3z(BApplication Management(3z (Bchiefly targets practitioners, users and decision-makers in the IT management sector. To lecturers and students of information management, business studies and related disciplines it is also of interest. Editors Prof. Frank Keuper holds the chair in business administration, especially convergence management and strategic management at Steinbeis University, Berlin. He is also academic head and director of the Sales & Service Research Center (partner of Telekom Shop Vertriebsgesellschaft mbH) and the T-Vertrieb Business School (partner of Telekom Deutschland GmbH). Christian Oecking is Chairman of the Management Board at Siemens IT Solutions and Services GmbH. Andreas Degenhardt is Head of Global Application Management at Siemens IT Solutions and Services GmbH.s
Keywords: Economics; Management information systems; Economics/Management Science; Business Information Systems